2008
DOI: 10.1098/rsbl.2008.0258
|View full text |Cite
|
Sign up to set email alerts
|

Selection on personality in a songbird affects maternal hormone levels tuned to its effect on timing of reproduction

Abstract: The increase or decrease in yolk androgens over the laying sequence of a clutch in birds may mitigate or enhance, respectively, the disadvantage of the last-hatched chicks, providing a potentially adaptive tool to adjust brood size to food conditions. This variation may involve a genetic component on which Darwinian selection can act. We found that two lines of a wild bird species selected for bold and shy personalities show, respectively, increased and decreased androgen concentrations over the laying sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 22 publications
3
34
2
Order By: Relevance
“…Importantly, a high consistency of yolk T deposition within females and between mothers and daughters does not preclude a plastic and adaptive female response to environmental variation, but in addition, it opens up the opportunity for hormone-mediated maternal effects to respond to selection and thus to evolve. Such indirect genetic effects can modify or accelerate phenotypic change in natural populations and might thereby play an important role in evolutionary processes such as parentoffspring coevolution (Kölliker et al 2000(Kölliker et al , 2005Müller et al 2007;Tschirren and Richner 2008), the evolution of behavioral syndromes (Dingemanse et al 2003;van Oers et al 2004;Groothuis and Carere 2005;Gil and Faure 2007;Tobler and Sandell 2007;Groothuis et al 2008), or dispersal behavior and the colonization of new environments (Hahn et al 2005;Duckworth and Badyaev 2007;Tschirren et al 2007) in a range of taxa. We hope that by elucidating the heritable basis of yolk hormone deposition, this study will bring us closer to an understanding of the evolution of hormone-mediated maternal effects, the patterns that shape their current expression both within and among species, and their consequences for the direction and speed of phenotypic change in natural populations.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a high consistency of yolk T deposition within females and between mothers and daughters does not preclude a plastic and adaptive female response to environmental variation, but in addition, it opens up the opportunity for hormone-mediated maternal effects to respond to selection and thus to evolve. Such indirect genetic effects can modify or accelerate phenotypic change in natural populations and might thereby play an important role in evolutionary processes such as parentoffspring coevolution (Kölliker et al 2000(Kölliker et al , 2005Müller et al 2007;Tschirren and Richner 2008), the evolution of behavioral syndromes (Dingemanse et al 2003;van Oers et al 2004;Groothuis and Carere 2005;Gil and Faure 2007;Tobler and Sandell 2007;Groothuis et al 2008), or dispersal behavior and the colonization of new environments (Hahn et al 2005;Duckworth and Badyaev 2007;Tschirren et al 2007) in a range of taxa. We hope that by elucidating the heritable basis of yolk hormone deposition, this study will bring us closer to an understanding of the evolution of hormone-mediated maternal effects, the patterns that shape their current expression both within and among species, and their consequences for the direction and speed of phenotypic change in natural populations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies measuring the development of personality tend to focus on unitary organisms and the role of early experience (DiRienzo et al, 2012), maternal effects (Groothuis et al, 2008) and persistence across life stages (Bell and Stamps, 2004). It has been shown that the consistency of personality can vary through ontogeny and upon maturation.…”
Section: Defining and Evaluating Collective Personalitiesmentioning
confidence: 99%
“…allocation of higher levels of T in first-laid eggs, could exacerbate disadvantages for later hatchlings, facilitating brood reduction under bad food conditions [63]. In this latter case, the higher levels of maternally-derived T in the first-laid eggs would boost the competitive ability of the first-hatched chicks and precipitate brood reduction via the death of the less competitive chick(s) hatched from the last-laid egg(s) [9], [56].…”
Section: Introductionmentioning
confidence: 99%